ANALISIS MAKNA DAN MOTIF KEPUTUSAN PEMBELIAN OFFICIAL MERCHANDISE BTS PADA ARMY KEDIRI - Pravitasari, Mei; Fauji, Diah Ayu Septi; Kurniawan, Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
It is interesting for researchers to analyze the purchase decision of BTS's official merchandise at ARMY Kediri. The purpose of this study is to analyze the meaning and motives of BTS's official merchandise purchase decisions at ARMY Kediri. The method in this study is qualitative with a phenomenological paradigm. The data collection process was carried out by conducting interviews with Kediri ARMYs who have an official BTS merchandise collection of five people. In this study, data analysis was carried out using working papers to facilitate the mapping of noema, epoche, noesis, intentional analysis, and eidetic reduction. This research resulted in the decision to purchase BTS's official merchandise at ARMY Kediri as a form of support and appreciation for BTS's work. By purchasing official BTS merchandise, fans feel satisfaction because their wishes are fulfilled. In addition, ARMY Kediri purchases official BTS merchandise as a form of identity that he is a BTS fan. The purchase of BTS official merchandise is done as a form of investment, some BTS official merchandise collections can be sold again in the future at a higher price.